PENGARUH PEMBERIAN SNACK BAR ALMORA TERHADAP PERUBAHAN KADAR KOLESTROL PEGAWAI DI UPTD PUSKESMAS SIDO MULYO KABUPATEN BANYUASIN - Izuddin, yana_180483 (JURNAL SVASTA HARENA RAFFLESIA, 2025)
Hypercholesterolemia is a lipid metabolism disorder characterized by an increase in total blood cholesterol levels, which is defined as total cholesterol above 200 mg/dL, low-density lipoprotein (LDL) above 160 mg/dL, and high-density lipoprotein (HDL) below 40 mg/dL. One of the necessary treatments to maintain stable cholesterol levels in individuals with hypercholesterolemia is the intake of fiber from legumes such as almonds, rolled oats, and red beans, which are processed into Almora Snack Bars and are known to help reduce cholesterol levels. Research Objective: reduction of cholesterol levels among employees at the Sido Mulyo Community Health Center in Banyuasin Regency. Research Method: The study used a quasi-experimental design with a two-group pretest-posttest approach and employed random sampling involving 60 respondents, all employees of the Sido Mulyo Health Center. Employees with high cholesterol levels were given Almora Snack Bars as a morning snack and tested using appropriate statistical methods. Research Results: The results of the paired t-test analysis showed a p-value of less than 0.05 for total cholesterol, LDL, HDL, and triglyceride levels in the treatment group, indicating significant differences before and after the intervention. The independent t-test also showed significant reductions in total cholesterol, LDL, HDL, and triglyceride levels (p-value < 0.05). Conclusion: The administration of 50 grams of Almora Snack Bar daily for 14 days had a significant effect on Change in cholesterol levels levels among the employees of the Sido Mulyo Community Health Center in Banyuasin Regency..